The COUP transcription factor binds to an upstream promoter element of the rat insulin II gene. - Hwung, Y P (1988)
Band-shifting and DNase I-footprinting assays have been used to study the trans-acting factor(s) binding to an important promoter element (-53 to -46 relative to the transcription start) of the rat insulin II gene. A binding activity which footprints a region between -60 and -40 was found in both HIT, a hamster insulinoma cell line, and HeLa cells. A mutation within this region which drastically decreases promoter activity in vivo also greatly reduces binding activity in vitro. This binding activity was purified from HeLa cells and identified by competition and renaturation analyses as being the same as the COUP (chicken ovalbumin upstream promoter) transcription factor, a DNA-binding protein required for efficient transcription of the ovalbumin gene in vitro. Interestingly, the binding sequences of the COUP transcription factor in the ovalbumin and the insulin promoters have only limited similarities.